DEVELOPMENT OF ENGLISH E-BOOK USING ASSURE MODEL AT BORNEO ENGLISH COURSE PALANGKA RAYA FOR ELEMENTARY LEVEL - Ikrimah, Ikrimah; Soraya, Rika; Aslamiyah, Suaibatul; Handayana, Eva; Alpian Sari, Muhammad; Siagian, Netty; Norefendi, Norefendi; Nadira, Parya; H.K, Salamah; Misrita, Misrita (Journal Compound: Improving the Quality of English Education, 2023)
This subject's goal was to create an English e-book by using ASSURE model at Borneo English Course Palangka Raya for elementary level; modules for understanding research methods were made by implementing the ASSURE model, which included the procedures listed: (1) Analyze the Learner; (2) State Standards and Objectives; (3) Choose Methods; Media or Materials; (4) Utilize Media and Materials; (5) Require Learner Participation; and (6) Evaluate and Revise. This book was developed by the 9 experts. They used book creator as the website in making the e-book. The e-book was supported by the use of Google Form, Google Docs, and hot potatoes app for developing and creating the book. This book was provided for Borneo English Course students who took the elementary level program. Borneo English Course was a course which provided English language teaching. This research was able to improve the students’ English by using English e-book.